Pelatihan Membuat Canang Pada Kegiatan Pasraman Kilat Untuk Meningkatkan Sradha dan Bhakti Siswa di SMK Bali Dewata - Gusti Ayu Putu Paramita Sari Dewi; Ngakan Putu Darma Yasa (UNHI Press, 2026)
Balinese Hindu culture contains various forms of local wisdom with significant contributions and potential that need to be preserved, one of which is canang. Canang is a form of offering that carries spiritual meaning and aesthetic value in Balinese Hindu religious traditions. However, along with the development of modern technology, the interest and ability of the younger generation in making canang sari has gradually declined. The purpose of this community service activity is to provide training in making canang sari for participants of the Pasraman Kilat program at SMK Bali Dewata. This activity serves as an effort to preserve culture and improve the religious skills of Hindu students. The materials provided include knowledge about the philosophy, materials, and practical techniques for making canang sari. The methods applied in this activity are lectures, demonstrations, and direct practice. The expected outputs of this community service include training on making canang sari and a community service journal article as part of the implementation of the Tri Dharma of higher education. The Pasraman Kilat activity contributes as a medium for strengthening cultural and spiritual values within the Hindu educational environment and supports the preservation of Balinese cultural heritage.